(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1854)
David Laing presents a petition from the inhabitants of Leith to General Monk that he suggests should be dated to c.1655-56. The petition is asking if General could remove his soldiers from the parishioners’ church so they could use it for worship. Laing also includes several entries from the Kirk-Session Records of the Church of St. Mary’s in South Leith to illustrate the difficulties the parishioners faced over the six years they were prevented from entering their church.